CRITICAL REFLECTION ON CLT APPLICATION IN INDONESIA - Abdul Halim (Shautut Tarbiyah, 2011)
There has been a social turn in current foreign language education ingeneral and communicative language teaching (CLT) in particular. Formany people, CLT might be regarded as a way to facilitate the targetlearners to acquire and employ the target language communicatively.Despite all CLT’s favourable characteristics and the fact that itcaptures the fundamental nature of language use for communicativesituations of everyday life, its implementation in Indonesian contextshas not been without problems. This is due to the fact that many peoplein Indonesia might still have different interpretation of applying CLTin the classroom setting.Key words: reflection, communicative, language, teaching, Indonesia